2009
DOI: 10.1002/app.31206
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion binding properties of novel wool powders

Abstract: Wool fibres have shown potential for the removal and recovery of toxic chemical and metal ions; however, their slow kinetics of binding has limited their widespread application. In this study three wool powders have been prepared from chopped wool fibre using various milling operations. Brunauer, Emmett, Teller analysis (BET) showed negligible change in surface area and Positron annihilation lifetime spectroscopy indicated no change in nanoporosity of the powders on processing. Binding of the transition metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Two peaks at 1,641 cm −1 (amide I) and 1,512 cm −1 (amide II) designated for -CONH 2 (Asparagine and Glutamine) and -CONH-(Peptide chains), respectively, as well as a strong peak appears at 1,439 cm −1 for -COOH (Aspartate and Glutamate acids). Finally, a prominent peak at 1,066 cm −1 for -CH 3 group (Alanine, Valine, Methionine, and Leucine) [25,28,34].…”
Section: Adsorption/desorption Repetition Investigationmentioning
confidence: 98%
See 1 more Smart Citation
“…Two peaks at 1,641 cm −1 (amide I) and 1,512 cm −1 (amide II) designated for -CONH 2 (Asparagine and Glutamine) and -CONH-(Peptide chains), respectively, as well as a strong peak appears at 1,439 cm −1 for -COOH (Aspartate and Glutamate acids). Finally, a prominent peak at 1,066 cm −1 for -CH 3 group (Alanine, Valine, Methionine, and Leucine) [25,28,34].…”
Section: Adsorption/desorption Repetition Investigationmentioning
confidence: 98%
“…Many researchers have tried to produce wool powder by different methods, such as regeneration from keratin solution, mechanical attrition, and chemicalmechanical techniques [21][22][23][24]. Recent studies showed improvement in wool surface reactivity by converting fibers into fine powder [25][26][27]. For example, the dye uptake of wool powder was found very high compared with wool fiber or activated charcoal under the same condition.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…They removed around 72 to 94% metals (Ca, Mg, Fe and Mn) from water at a pH of 6-9 within 20-30 minutes 59 . Milled wool or hair powder dramatically increased the rate of metal ion absorption 70,71 ; for example, milled wool powder showed ~42 fold higher uptake of Cu than that of the wool fiber 70 .…”
Section: Keratin Particlesmentioning
confidence: 99%
“…Generating a fibrous powder from silk and wool fibres can dramatically enhance features such as rate and selectivity of metal binding properties. 3,4 PALS was used to evaluate the change in microporosity of fibres compared to jet-milled particles. PALS showed no change in size or incidence of micropores in natural fibres compared to milled samples.…”
Section: Porosity and Palsmentioning
confidence: 99%